Effects of ozone treatment on the physicochemical and functional properties of whole grain flour. (May 2018) - Obadi, Mohammed; Zhu, Ke-Xue; Peng, Wei; Sulieman, Abdellatief A.; Mohammed, Khalid; Zhou, Hui-Ming
Abstract: We examined the physicochemical and functional properties of whole grain flour (WGF) treated with ozone gas at 5 g/h for 0, 5, 15, 35, and 45 min. The water and oil absorption, swelling power, and solubility all increased significantly with increasing ozonation time, while the pasting properties showed significant decreases in peak viscosity, trough, breakdown, final, and setback viscosity values (all p  ≤ 0.05). Structural analysis revealed changes in the intensities of the O–H, C–H, and CH2 bending vibrations of protein side chains and lipids with increasing ozonation time. Ozone affected the mean particle size of WGF. Confocal laser scanning microscopy examination of WGF revealed remarkable differences between control and treated flours. Highlights: Ozonation increased the water and oil absorption capacity of flour. Exposing WGF to ozone gas for a short period of time enhanced the Pasting properties. Ozone changed the structure of starch and proteins in WGF.